2010
DOI: 10.1584/jpestics.g10-10
|View full text |Cite
|
Sign up to set email alerts
|

A new endosulfan-degrading fungus, Mortierella species, isolated from a soil contaminated with organochlorine pesticides

Abstract: Two new aerobic endosulfan-degrading fungal strains, Mortierella sp. strains W8 and Cm1-45, were isolated from soil contaminated with organochlorine pesticides. This is the first report on the biodegradation of endosulfan by Zygomycota. The strains isolated in this work degraded more than 70% and 50% of a and b-endosulfan, respectively, over 28 days at 25°C, whereas 8.2 mM of each a and b-endosulfan was added as the initial concentration in liquid cultures. Only a small amount of endosulfan sulfate, a persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…45 Figure S8-3 shows the MS corresponding to R t = 4.225 min, and it exactly matches with the m / z patterns of acetophenone with a probability of 70%. 45 The observed mass fragments are m / z = 120 (M + ), 105 (M–CH 3 CO + ; C 7 H 5 O + ), 77 (C 6 H 5 + ), and 43 (CH 3 CO + ). The mass spectrum of the next feature that appeared at R t = 4.42 min (Figure S8-4) matches with that of 2-phenyl-2-propenol with a probability of 92%; this feature shows a parent peak at m / z 136 (M + =C 9 H 12 O + ), and the following fragment peaks appeared at m / z 121 (M + –CH 3 ), 118 M + –H 2 O), 103 (C 8 H 7 + ), 91 (C 7 H 8 + ), 77 (C 6 H 5 + ), and 43 (CH 3 CO + ).…”
Section: Dye-sensitized Solar Cellssupporting
confidence: 54%
See 1 more Smart Citation
“…45 Figure S8-3 shows the MS corresponding to R t = 4.225 min, and it exactly matches with the m / z patterns of acetophenone with a probability of 70%. 45 The observed mass fragments are m / z = 120 (M + ), 105 (M–CH 3 CO + ; C 7 H 5 O + ), 77 (C 6 H 5 + ), and 43 (CH 3 CO + ). The mass spectrum of the next feature that appeared at R t = 4.42 min (Figure S8-4) matches with that of 2-phenyl-2-propenol with a probability of 92%; this feature shows a parent peak at m / z 136 (M + =C 9 H 12 O + ), and the following fragment peaks appeared at m / z 121 (M + –CH 3 ), 118 M + –H 2 O), 103 (C 8 H 7 + ), 91 (C 7 H 8 + ), 77 (C 6 H 5 + ), and 43 (CH 3 CO + ).…”
Section: Dye-sensitized Solar Cellssupporting
confidence: 54%
“…It requires several days to degrade ES into its fragments and involves several steps to grow the microorganism in a suitable environment. 45 It is further limited by low degradation efficiency with high toxic metabolites, and hence a complete mineralization by cheap alternative methods, such as photocatalysis, is required. 46 Thomas et al, reported photocatalytic activity studies of Ag- and Au-incorporated TiO 2 for degradation of ES under solar light irradiation.…”
Section: Dye-sensitized Solar Cellsmentioning
confidence: 99%
“…Many mortierellean species showed potential as very interesting fungi for biotransformations and biotechnological applications [ 24 ]. Kataoka et al [ 25 ] have isolated endosulfan-degrading Mortierella species from a soil contaminated with organochlorine pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…However, these metabolites are less toxic [8] . There are many reports on the degradation of endosulfan by bacteria [9] . Klebsiella pneumoniae has the capability to biologically degrade (biodegradation) endosulfan.…”
Section: Introductionmentioning
confidence: 99%